Multimodality in discussion sessions: corpus compilation and pedagogical - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Mercedes Querol-Julián Universitat Jaume I, Spain   ABSTRACT Discussion sessions of conference paper presentations are spontaneous and unpredictable, in contrast to the prepared lecture that precedes them. These can be challenging, especially for novice presenters whose worst fear is to fail to understand the second meaning of a question or comment, and who know it is not only the quality of the research that is judged but also their prestige and worth. Additionally, spoken academic genres have traditionally been explored by focusing on the transcription of speech and disregarding the multimodal nature of spoken discourse. This study offers a comprehensive account of the design of a multimodal corpus of discussion sessions, where audio, video, transcriptions and annotations are time-synchronised. This multilayer analysis provides examples (not only of linguistic utterances of rhetorical moves and multimodal evaluation, but also of how they are actually expressed paralinguistically and kinetically), which can be used in the classroom and to design learning-teaching materials.